SHIELDING THOSE WHO HIGHLIGHT THE EMPEROR’S NEW CLOTHES – DOES THE CONSTITUTION DEMAND A JOURNALISTIC PRIVILEGE? (The Pretoria Student Law Review, 2021)
In his judgment in the English case of R v Derby MC, ex parte B,  the then Lord Chief Justice of England, Lord Taylor, stated that legal professional privilege was a ‘fundamental condition on which the administration of democracy as a whole rests’. This privilege holds that a legal practitioner may not, without the leave of his client, answer any question addressed to him on the witness stand regarding information provided by the client. Thus, in the interests of justice, we allow (even force) a witness who may have crucial information on the matter at hand to refuse to provide such information. Whilst on similar lines English law recognises a journalistic privilege, South African law recognises no journalistic privilege. This means that when a journalist is asked a question whilst on the witness stand, they must answer that question. This includes questions regarding journalistic sources. Failure to answer any such question is harshly penalised, including imprisonment for up to five years. At the heart of the matter is this: Should a journalist ever be forced to reveal his or her sources in the preparation of an article? Journalists need sources to enable them to produce stories. The term ‘off the record’ is synonymous with journalism, and one must wonder how many people would provide journalists with information if there was a chance that their identity could or might be made public. Stated differently, how many more people would provide journalists with material if they knew that a journalist could not be compelled to reveal their identity? In its current state, both South African criminal and civil law offer mechanisms designed to compel witnesses to answer questions posed to them by sanctioning a refusal to answer a question with detention In the absence of a recognised journalistic privilege, journalists, if asked about their sources, must answer the question posed to them or risk being incarcerated. This clearly places journalists in a Catch22 type of situation: risk your career for revealing your sources or your liberty for not.
Keywords: R v Derby; legal professional privilege; English law; journalistic privilege; South African law; journalistic sources; compel witnesses to answer questions